Anthropogenic biomes found in rangelands globally - Getahun, Yasin; Flintan, Fiona E. (International Livestock Research Institute, 2018)
This map shows global historic" Anthropogenic Biomes" of the world (as mapped by Ellis et al 2000) that exists within rangelands, selected classes are: Pastoral Villages, Residential Rangelands, Populated Rangelands and Remote Rangelands. The mapping of the rangelands is taken from rangeland types and boundaries previously mapped by University of Idaho and the Society for Rangeland Management (SRM). Country boundaries were taken from ESRI 2016.